Critically evaluate how and why suppliers circumvent complaince codes. To what extend are social audit frameworks effective in managing sourcing risks. - Chen, yusheng (2006)
Sustainability and outsourcing management are both complex areas, but the combination of both is where business, value creation and competitiveness meet reality. It is difficult to manage increasing globalised supply chains. The purpose of this management project is to critically examine the supply chain risk management system of many branded companies or retailers, particularly, social auditing (SA) or called social assessment, as to its effectiveness and appropriateness in managing sourcing risks. From the literature review and some consultations, the characteristic of SA is one of the best instruments to measure a company's integrity and genuine activities. However, it has drawbacks of auditor quality, risks of biased information and most important, the manipulative data. The project proceeds from a case study referring to understand why and how factory managers circumvent the codes, and how to improve the SA framework in order to enhance the sustainability of sourcing practices. The project found out four common manipulation techniques in exercise, namely bribery, falsified record, worker coaching and threatening and complicit coalition. Furthermore, the fundamental problem is the contradiction between the buyer principles and their ethical standards, which needs thorough scrutiny before implementing the social audit assessment.